Proceedings of the Third International Conference on Sustainable Innovation 2019 – Health Science and Nursing (IcoSIHSN 2019) 2019
DOI: 10.2991/icosihsn-19.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Social Support and Anxiety in Mothers of Children with Acute Lymphoblastic Leukemia

Abstract: The incidence of acute lymphoblastic leukemia cancer continues to increase every year. Child with cancer and undergoing therapy causes anxiety for parents such as sleep disorder, inability to make decisions, and panic. Severe anxiety contributes to decrease quality of life. Factors that are needed in reducing anxiety are religiosity and social support. The main objective was analyzed the relationship of religiosity and social support with the anxiety of mothers. This research employed cross sectional design. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…[ 9 10 11 ] Studies have also shown that spirituality plays an essential role in adapting to stressful life conditions caused by chronic disorders. [ 12 13 14 15 16 ] Parents of children with cancer also tend to spirituality in the face of difficult life situations and use it as a suitable source to cope with stressful conditions. [ 17 ] Some studies have indicated that spirituality has an important role in helping parents of children with cancer and causes them to feel calm and comfort and also reduce anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 10 11 ] Studies have also shown that spirituality plays an essential role in adapting to stressful life conditions caused by chronic disorders. [ 12 13 14 15 16 ] Parents of children with cancer also tend to spirituality in the face of difficult life situations and use it as a suitable source to cope with stressful conditions. [ 17 ] Some studies have indicated that spirituality has an important role in helping parents of children with cancer and causes them to feel calm and comfort and also reduce anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Some studies have indicated that spirituality has an important role in helping parents of children with cancer and causes them to feel calm and comfort and also reduce anxiety and depression. [ 14 17 18 ] Hence, spiritual care is a necessity for achieving proper control and management of the situation and accepting the disease by the parents. To organize spiritual care, the spiritual needs of parents should first be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian ini penulis berfokus pada dukungan sosial dan religiusitas dengan pertimbangan kedua faktor tersebut memiliki pengaruh positif terhadap kecemasan seseorang menghadapi situasi pandemi Covid 19 saat ini. Fetriyah, Mahmudah, Damayanti & Firdaus (2019) menyatakan bahwa dukungan sosial menjadi salah satu faktor utama untuk mengurangi kecemasan. Hal tersebut sesuai pernyataan Han, Yan, Zhang, Zhao, Sun, Li, Lei, Liu & Chen (2014) mengemukakan bahwa dukungan sosial mempengaruhi gejala kecemasan seseorang.…”
unclassified